Mini Review: Hypocholesterolemic Potential of Unsaponifiable Matter from Palm Fatty Acid Distillate - wulansari, angela; Estiasih, Teti; Yunianta, Yunianta (Program Studi Teknologi Pangan, 2019)
Palm fruit as raw material of palm oil is the main commodity of Indonesian agriculture. Palm fatty acid distillate (PFAD) is a by-product of palm oil refinery process in deodorization stage. PFAD contained bioactive compounds such as vitamin E, phytosterols, and squalene. Vitamin E, phytosterols, and squalene have knows for its hypocholesterolemic effect and cardio protector. Bioactive compounds of PFAD can be separated from its fatty acid using saponification reaction. Saponification of PFAD produced unsaponifiable matter (USM) whichÂ was rich in bioactive compounds. Food fortification is aimed to enhance the nutrition quality of food for specific reason. The fortificant can be macronutrient or micronutrient. USM of PFAD potentially become food product fortificant which will give hypocholesterolemic effect. This review is discussed about hypocholesterolemic effect of each bioactive compounds in USM of PFAD and the potential of USM as food fortificantÂ espsecially for food with hypocholesterolemic effect.